الزكاة كاستراتيجية جديدة للتخفيف من نسبة البطالة في الجزائر - مراد، شريف (جامعة محمد بوضياف المسيلة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2017)
Zakat according to the jurisprudents and scholars of religion is a right to God Almighty, who imposed it in the funds of Muslims thanks to his grace and close to him and recommending the same and money and given to those named in his book of the poor and the poor and other categories receivable. Zakat is a financial obligation imposed by the State or its representative on behalf of the public or individuals, forcibly and definitively, without any specific remuneration, and is imposed by the State in accordance with the capacity of the taxpayer, but it is used to cover the expenses of the eight banks specified in the Koran or to meet the requirements of the policy Public Finance of the State. Therefore, it is possible to say that zakat is an important economic resource that redistributes wealth in a fair manner. The role of this financial institution (zakat) has disappeared over time. This is due to the individual distribution of Zakat. However, with the establishment of Zakat funds in Islamic countries in general In particular, in Algeria, zakat has become a tool in the process of social and economic development, reflecting its role in the zakat funds, which have been used by most Islamic countries as an effective tool to alleviate the problems of unemployment by supporting small enterprises that create jobs. This is Strategy, which contributed to the reduction of the unemployment problem by supporting youth employment in various mini-loans that contributed to the opening workshops and units of production, which contributed to providing jobs, helping to raise the social and local economic development and thus achieving sustainable development.
تعتبر الزكاة حسب فقهاء الشريعة وعلماء الدين حق لله تعالى الذي فرضه في أموال المسلمين شكرا لنعمته تعالى وتقربا إليه وتزكية للنفس والمال وتعطى لمن سماهم في كتابه من الفقراء والمساكين وسائر الفئات المستحقة. إذن فالزكاة هي فريضة مالية تقتطعها الدولة أو من ينوب عنها من الأشخاص العامة أو الأفراد قسرا وبصفة نهائية ودون أن يكون لها مقابل معين، وتفرضها الدولة طبقا لقدرة الممول التكليفية إلا أنها تستخدمها في تغطية نفقات المصارف الثمانية المحددة في القران الكريم أو الوفاء بمقتضيات السياسة المالية العامة للدولة. إذن من خلال ما سبق يمكن القول أن الزكاة عبارة عن مورد اقتصادي هام يعمل على إعادة توزيع الثروة بطريقة عادلة، وقد غيب دور هذا الجهاز المالي (الزكاة) على مر الأزمنة وهذا بسبب التوزيع الفردي للزكاة، إلا انه ومع إنشاء صناديق الزكاة في الدول الإسلامية بصفة عامة وفي الجزائر بصفة خاصة، أصبحت الزكاة أداة في عملية التنمية الاجتماعية والاقتصادية، حيث تجسد دورها في صناديق الزكاة التي أصبحت تستخدمها معظم الدول الإسلامية كأداة فعالة للتخفيف من مشاكل البطالة وذلك عن طريق دعم المشروعات الصغيرة التي تخلق مناصب شغل. وخير مثال على ذلك الجزائر التي اتبعت هذه الاستراتيجية والتي ساهمت في التخفيض من مشكل البطالة عن طريق دعم تشغيل الشباب بمختلف القروض المصغرة التي ساهمت في فتح ورشات ووحدات إنتاجية مما ساهم في توفير مناصب شغل مما ساهم في رفع التنمية المحلية الاجتماعية والاقتصادية وبالتالي تحقيق التنمية المستدامة.
Keywords: صناديق الزكاة -- ظاهرة البطالة -- التنمية الاقتصادية -- الاقتصاد الجزائري